Persepsi Siswa Terhadap Perpustakaan SMP Negeri 16 Padang - Oktavia, Rika; Desriyeni, Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2015)
The purposes of writing of this paper are (1) to know students perception about the library in SMP Negeri 16 Padang that is observed from the collection aspect; (2) to know students perception about the library in SMP Negeri 16 Padang that is observed from librarians aspect; (3) to know students perception about the library in SMP Negeri 16 Padang that is observed from the lay out. The form of research is descriptive quantitative. The technique of data collection is done by using questionnaire and interview. The subjects of this researc are 7th grade student, 8th grade student, and also the librarian in SMP Negeri 16 Padang. Based on the research, can be concluded: (1) the perception of the student about the library of SMP Negeri 16 Padang that is observed from collection side, most of students (53%) stated that the book collection in SMP Negeri 16 Padang is appropriate with the learning needs; (2) from the librarians aspect, most of student (61%) stated that the librarian of SMP Negeri 16 Padang is friendly; (3) from the lay out aspect, half of students number are disagree about the arrangement of book racks, tables and chairs in the library of SMP Negeri 16 Padang due to the library is so crowded and it makes the students do not comfortable to visit the library. Keywords: perception, library, student.